Genome, host genome integration, and gene expression in Diadegma fenestrale ichnovirus from the perspective of coevolutionary hosts - Kim, Juil; Rahman, Md-Mafizur; Kim, A-Young; Ramasamy, Srinivasan; Kwon, Min; Kim, Yonggyun (Frontiers in Microbiology, 2023)
Polydnaviruses (PDVs) exhibit species-specific mutualistic relationships with endoparasitoid wasps. PDVs can be categorized into bracoviruses and ichnoviruses, which have independent evolutionary origins. In our previous study, we identified an ichnovirus of the endoparasitoid Diadegma fenestrale and named it DfIV. Here, DfIV virions from the ovarian calyx of gravid female wasps were characterized. DfIV virion particles were ellipsoidal (246.5  109.0 nm) with a double-layered envelope. Next generation sequencing of the DfIV genome revealed 62 non-overlapping circular DNA segments (A1–A5, B1–B9, C1–C15, D1–D23, E1–E7, F1–F3); the aggregate genome size was approximately 240 kb, and the GC content (43%) was similar to that of other IVs (41–43%). A total of 123 open reading frames were predicted and included typical IV gene families such as repeat element protein (41 members), cysteine motif (10 members), vankyrin (9 members), polar residue rich protein (7 members), vinnexin (6 members), and N gene (3 members). Neuromodulin N (2 members) was found to be unique to DfIV, along with 45 hypothetical genes. Among the 62 segments, 54 showed high (76–98%) sequence similarities to the genome of Diadegma semiclausum ichnovirus (DsIV). Three segments, D22, E3, and F2, contained lepidopteran host genome integration motifs with homologous regions of about 36–46 bp between them (Diadegma fenestrale ichnovirus, DfIV and lepidopteran host, Plutella xylostella). Most of the DfIV genes were expressed in the hymenopteran host, and some in the lepidopteran host (P. xylostella), parasitized by D. fenestrale. Five segments (A4, C3, C15, D5, and E4) were differentially expressed at different developmental stages of the parasitized P. xylostella, and two segments (C15 and D14) were highly expressed in the ovaries of D. fenestrale. Comparative analysis between DfIV and DsIV revealed that the genomes differed in number of segments, composition of sequences, and internal sequence homologies.